The importance of English subjects at the primary level: Stakeholders’ perceptions - Nida Husna; Anni Rachmayani; Reza Anis Maulidya; Fahriany Fahriany (Studies in English language and education, 2025)
This study investigates how stakeholders perceived the inclusion of English subjects as part of local content in primary schools. A qualitative method employing a descriptive approach was used to conduct the research. Data were collected through interviews and questionnaires. Participants involved in this study included primary school teachers, a vice principal for curriculum affairs, English teachers, and primary school students. The research focused on three primary schools—located in Depok, Bogor, and Sukabumi—to explore stakeholders’ perspectives. The results reveal a positive consensus among stakeholders regarding the significance of English education in primary schools for enhancing students’ foundational vocabulary. Nevertheless, stakeholders expressed concerns about the designation of English as a local content subject in these schools. The study highlights the vital roles each stakeholder plays in improving the quality of English teaching and students’ language skills. Despite challenges in teaching and learning English, educators and students have implemented strategies for improvement, including participation in teacher associations, engaging in English tutoring, watching English media, and listening to English songs. Based on these findings, the study emphasizes the urgency of integrating English subjects into the school curriculum to support students’ skills. This study, which focuses on private primary schools, calls for future investigations into the implementation of English subjects in public primary schools.